The empowerment perspective of implementation one house one jumantik (G1R1J) in sub-urban area - Isnani, Tri; Ramadhani, Tri; Ikawati, Bina (Universitas Gadjah Mada, 2024)
Purpose: To examine the effectiveness of one house one larva monitor program as a community empowerment. Methods: The research was conducted using the PAR approach by collecting data by observation, in-depth interviews, and discussions with samples/informants including health workers at the public health center, cadres/jumantik, jumantik rumah, community leaders, and local village and sub-district government figures. The team formed jumantik followed by training and assistance for five months for jumantik. The research location is in an urban village in Mempawah Regency, West Kalimantan Province, with data collected from March to October 2019. Results: The research location is an area with a socio-cultural geographical character that is between rural and urban characters. Knowledge about dengue fever and G1R1J is still lacking. Problems in the implementation of G1R1J are related to participation issues, namely the awareness and acceptance of residents towards activities, replacement of cadres/volunteers, and wrong perceptions. Socialization, which is the first step in empowerment, has not been carried out. Socialization is also a step in growing knowledge and awareness that will influence the growth of community participation. Conclusion: The problems faced include the problem of participation of cadres and community members. The socialization stage as the introduction stage influences knowledge and behavior. The condition of the community as social capital is incredibly supportive in empowerment. Empowerment requires adjustment to each condition. Therefore, mapping of initial conditions and comprehensive mass outreach is needed.